2018
DOI: 10.1515/ijcre-2017-0256
|View full text |Cite
|
Sign up to set email alerts
|

Production of NMSBA from NMST Catalyzed by Co/Mn/Br and HPW@C Modified with ZnCl2 Solution

Abstract: Abstract2-nitro-4-methylsulfonylbenzoic acid (NMSBA) can be produced by oxidizing 2-nitro-4-methylsulfonyltoluene (NMST) with air catalyzed by Co/Mn/Br and phosphotungstic acid(HPW) loaded on activated carbon. This paper reports that the catalytic ability of the HPW@C catalyst in the oxidation of NMST to NMSBA can be improved by treating the activated carbon with ZnCl2solution. The best modification condition with ZnCl2solution is impregnating the carbon sample in 0.1 mol/L solution for 6 h followed by calcina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It can be seen from Table 2 that the ratio of molybdenum to tungsten in the H 3 PMo x W 12Àx O 40 synthesized by ether extraction method is very close to the theoretical value, and the deviation is very small. The ICP characterization data show that the mass fractions of molybdenum and tungsten atoms in the samples conform to the [XM 12 O 40 ] nÀ . Therefore, it can be concluded that the prepared phosphomolybdenum tungsten heteropoly acids have Keggin type structure.…”
Section: Effect Of Mo/w Ratiomentioning
confidence: 89%
See 2 more Smart Citations
“…It can be seen from Table 2 that the ratio of molybdenum to tungsten in the H 3 PMo x W 12Àx O 40 synthesized by ether extraction method is very close to the theoretical value, and the deviation is very small. The ICP characterization data show that the mass fractions of molybdenum and tungsten atoms in the samples conform to the [XM 12 O 40 ] nÀ . Therefore, it can be concluded that the prepared phosphomolybdenum tungsten heteropoly acids have Keggin type structure.…”
Section: Effect Of Mo/w Ratiomentioning
confidence: 89%
“…He et al [ 11 ] decreased the usage of H 3 PW 12 O 40 , accelerated NMST oxidation, and increased NMSBA yield with a heterogeneous catalytic system by immobilizing H 3 PW 12 O 40 on activated carbon. Wen et al [ 12 ] improved the catalytic capability of H 3 PW 12 O 4 @C by modifying the carbon with a ZnCl 2 solution. Liu et al [ 13 ] improved the catalytic activity of H 3 PMo 12 O 40 @C by introducing H 2 SO 4 , HCl, HNO 3 , CH 3 COOH, and H 2 C 2 O 4 into the solution as competitive adsorbates for H 3 PMo 12 O 40 in the preparation of H 3 PMo 12 O 40 @C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al 10 used H 2 SO 4 , HCl, HNO 3 , CH 3 COOH, and H 2 C 2 O 4 as competitive adsorbates in the preparation of H 3 PMo 12 O 40 @CAC to improve the catalytic ability of H 3 PW 12 O 4 @-CAC in the production of NMSBA. Wen et al 11 upgraded the NMSBA yield in the oxidation of NMST under the catalysis of H 3 PW 12 O 4 @CAC by treating the carbon with ZnCl 2 solution.…”
Section: Introductionmentioning
confidence: 99%